The power of Presence: Exploring experiences of therapy with a client suffering from a chronic neurological condition - Falzon, Rose (European Journal for Qualitative Research in Psychotherapy, 2021)
This article explores the applicability and effectiveness of the Gestalt paradigm in therapy involving clients with chronic and/or progressive physiological illnesses, a common occurrence in therapy. It presents a case study involving one particular client, Gary (pseudonym), as developed through an innovative process of collaboration between therapist and client. Gary’s three-year therapeutic journey following the diagnosis of his progressive neurological condition is captured via a methodology that incorporates features of Narrative Inquiry. After therapy ends, therapist and client join forces to re-explore the experience via discussions, meetings, journal writing and reflexivity. This joint endeavour then becomes the basis for the author’s exploration of the relevance and benefits of the Gestalt paradigm, her own favoured theoretical stance. Here, she argues, the focus of therapy is on staying in steadfast contact with the client in the here, rather than seeking to eradicate the problematic facets of chronic illness. On the basis of her work with Gary, who emerges with greater ability to manage his experiences, the author concludes that beneficial therapy is rooted in the resolute contact and the soulful presence of the ‘I and Thou’ relationship (Buber, 1958) and that the psychotherapeutic interventions that characterized her work with Gary have relevance for other clients confronting chronic physiological conditions.